2015
DOI: 10.1590/0037-8682-0027-2015
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of Helicobacter pylori strains to five antibiotics, including levofloxacin, in Northwestern Turkey

Abstract: Introduction: Antibiotic resistance is the main factor that affects the effi cacy of current therapeutic regimens against Helicobacter pylori. This study aimed to determine the rates of resistance to effi cacy clarithromycin, amoxicillin, tetracycline, levofl oxacin and metronidazole among H. pylori strains isolated from Turkish patients with dyspepsia. Methods: H. pylori was cultured from corpus and antrum biopsies that were collected from patients with dyspeptic symptoms, and the antimicrobial susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 35 publications
6
56
0
Order By: Relevance
“…An emerging appearance of H. pylori antibiotic resistance has also been reported from other parts of the world, including Asia, Europe, and the Americas 12,15–17,19,2628. This observation, coupled with reports of H. pylori reinfection after successful antibiotic treatment,6,7 makes H. pylori treatment more challenging.…”
Section: Discussionmentioning
confidence: 92%
“…An emerging appearance of H. pylori antibiotic resistance has also been reported from other parts of the world, including Asia, Europe, and the Americas 12,15–17,19,2628. This observation, coupled with reports of H. pylori reinfection after successful antibiotic treatment,6,7 makes H. pylori treatment more challenging.…”
Section: Discussionmentioning
confidence: 92%
“…In a southern region study, the levofloxacin resistance rate was 18.2% in 2012 [11]. A western region study reported the prevalence of resistance to levofloxacin as 29.5% (breakpoint MIC ≥1 mg/L) [19].…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, there are very few studies for levofloxacin resistance rates for H. pylori, and the overall resistance of H. pylori to levofloxacin was detected in 31 (23.7%, 95% CI: 18-30.2) of 1059 total H. pylori strains isolated in Turkey. In a north region study (2014), the prevalence of primary resistance to levofloxacin was detected as 29.5%, and the MIC 90 value was >32 mg/L (breakpoint MIC ≥1 mg/L) [19]. In a north region study (2014), the prevalence of primary resistance to levofloxacin was detected as 29.5%, and the MIC 90 value was >32 mg/L (breakpoint MIC ≥1 mg/L) [19].…”
Section: Prevalence Of the Primary Levofloxacin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…At present, the eradication of H. pylori infection is main troubles antibiotic resistance, patients compliance and intolerance to therapeutic regimens (Niv et al, 2015). Antibiotic resistance is nowadays a major concern since one of the major causes of treatment failure against the H. pylori is drugs sensitive to this germ are getting resistant Caliskan et al, 2015;Filipa et al, 2011). The causes of resistance are poor drug penetration, low drug concentration, short gastric residence time and antibiotic resistance represent a significant health care burden on society.…”
Section: Introductionmentioning
confidence: 99%